(untitled) (Tanzania Journal for Population studies and Development, 2017)
Increasing access to safe water remains a global priority even though the Millennium Development Goals more than halved the number of people lacking access to water. The Sustainable Development Goals, introduced in 2015, go further and seek universal access to a source of safe water located on premises. In Dar es Salaam, there is a significant gap between the number of households using safe water—meaning water free from contamination—and the number of households with a source of safe water on premises. Efforts to increase access on premises largely focus on expanding the city’s piped water network. Households lacking a direct connection to this network must rely on informal suppliers such as vendors, household resellers, and kiosks. Informal suppliers, also called small water enterprises, are an important part of increasing water access in areas not currently served by the piped network. Yet, as Dar es Salaam increases water access, these informal suppliers lose customers and income. This paper uses interviews with these suppliers to explain the impacts and causes of increased water access. It suggests ways that development policy can improve water access without harming these informal suppliers.